CHANGING PLACE: THE NEW INTERNATIONAL ORDER AND BRAZIL - Faria, Luiz Augusto (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
The fracture of the world order and the falling of US hegemony are the context in which Brazil’s national interest must be built. The possible change in its peripheric position to the place of a player with more global influence is examined. In order to do this, Brazilian relations with its Latin America and Caribbean neighbors are examined, and how they could help to redefine its place in the world order. Finally, this article will address domestic issues that affect foreign policy, by identifying the role of class struggle between different social forces that define our national social formation, its will for power in the world system and its international alliances for its repositioning in global hierarchy.